IMPROVEMENT OF ACCOUNTING AND REPORTING OF INTELLECTUAL PROPERTY OBJECTS ON THE BASIS OF THEIR HARMONIZATION AND STANDARDIZATION - BODNAR, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In today's conditions, intellectual property is becoming the most important factor in economic development. It is the scale and efficiency of intellectual capital that largely determine the level of competitiveness of products and enterprises as a whole. The relevance of the topic is growing, as intellectual property, has an increased ability to generate revenue, creates a basis for solving economic problems and reproduction of production. The complex process of increasing the efficiency of production through the introduction and use of intellectual property necessitates the need for reliable and complete information needed to make operational and strategic management decisions. Much of this information is provided by the accounting system. However, the issues of accounting for intellectual property in domestic science remain insufficiently studied. In particular, national accounting standards do not provide a thorough explanation of some aspects of the organization of intellectual property accounting, existing accounting models do not cover all the diversity and content of intellectual processes, there is no legally approved procedure for reflecting intellectual property as an object of accounting .In this regard, it is important to explore and address issues related to improving the accounting and reporting of intellectual property through harmonization and standardization.The article reveals the issues of economic essence of intellectual property, identifies the main problems in their accounting, considers the features of reporting in accordance with NP (S) BU and IFRS, the main areas of improvement of accounting and reporting of intellectual property.
Keywords: accounting; reporting; standardization; intellectual property